Designing Authentic Performance Tasks and Projects: Tools for Meaningful Learning and Assessment - Jay McTighe, Kristina J. Doubet, Eric M. Carbaugh (ASCD, 2020)
Aimed at the growing number of educators who are looking to move beyond covering the curriculum, Designing Authentic Performance Tasks and Projects provides a comprehensive guide to ensuring students' deeper learning—in which they can transfer their knowledge, skills, and understandings to the world beyond the classroom. Readers will learn how to* Create authentic tasks and projects to address both academic standards and 21st century skills. * Apply task frames to design performance tasks that allow voice and choice for students. * Design and use criterion-based evaluation tools and rubrics for assessment, including those for students to use in self-assessment and peer assessment. * Incorporate performance-based instructional strategies needed to prepare students for authentic performance. * Differentiate tasks and projects for all students, including those needing additional support or challenge. * Effectively manage the logistics of a performance-based classroom. * Use project management approaches to facilitate successful implementation of tasks and projects. * Develop performance-based curriculum at the program, school, and district levels. Authors Jay McTighe, Kristina J. Doubet, and Eric M. Carbaugh provide examples and resources across all grade levels and subject areas. Teachers can use this practical guidance to transform their classrooms into vibrant centers of learning, where students are motivated and engaged and see relevance in the work they are doing.